2008
DOI: 10.3748/wjg.14.6531
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal carcinoma in Lagos and Sagamu, Southwest Nigeria: A histopathological review

Abstract: CRC is the commonest malignant gastrointestinal (GIT) tumor most commonly located in the recto-sigmoid region. The age and sex prevalence and histopathological features concur with reports from other parts of the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
52
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 17 publications
14
52
4
Order By: Relevance
“…The 50 articles considered irrelevant did not comply with the exclusion/inclusion criteria set for this review; however, some were retained for extra information, mainly in the discussion. The 15 relevant articles [10,20,[32][33][34][35][36][37][38][39][40][41][42] were then supplemented by the 21 data sets secured with permission from the IARC [43,44] and the further 21 data sets which were received from the directors of the cancer registries through the IACR [16]. Six articles, which were not suitable for contribution to the estimates of incidence but were sourced for full-text copies, were retained for information on the biological characteristics of CRC diagnosed in SSA.…”
Section: Search Strategy For Systematic Analysis and Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 50 articles considered irrelevant did not comply with the exclusion/inclusion criteria set for this review; however, some were retained for extra information, mainly in the discussion. The 15 relevant articles [10,20,[32][33][34][35][36][37][38][39][40][41][42] were then supplemented by the 21 data sets secured with permission from the IARC [43,44] and the further 21 data sets which were received from the directors of the cancer registries through the IACR [16]. Six articles, which were not suitable for contribution to the estimates of incidence but were sourced for full-text copies, were retained for information on the biological characteristics of CRC diagnosed in SSA.…”
Section: Search Strategy For Systematic Analysis and Data Extractionmentioning
confidence: 99%
“…Since this initial commitment to reducing the burden of disease caused by NCDs the World Health Assembly has also endorsed the Global Strategy on Diet and Physical Activity and Health [10,11], and the Framework Convention for Tobacco Control [12].…”
Section: Search Strategy For Systematic Analysis and Data Extractionmentioning
confidence: 99%
“…[6][7][8] In Nigeria, Ibrahim et al found that 40% of all CRC cases observed in a 30-year period occurred in the final five years of the study (2004)(2005)(2006)(2007)(2008). Meanwhile the surgical biopsy registry at Lagos University Teaching Hospital has identified CRC as the third most commonly diagnosed malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Colorectal cancer (CRC) it the third most common cancer in men and the second most common cancer in women worldwide 4 and rising rates have been observed in LMIC. [5][6][7][8] There is a need to examine the etiology, presentation, biology and outcomes of CRC in LMIC and how it may differ from CRC in better-studied parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators have indicated that most of this increase in incidence was very likely associated with the populations' progressive adoption of a Western lifestyle and diet. Interestingly, in Africa, while the colorectal cancer incidence has been found to range from 3.7% to 10% of all diagnosed cancer, the cancers were seen to occur among a larger number of young patients (relative to the incidence in this population in Western countries) as well as among the increasingly urbanized populations (Abdulkareem et al 2008). As a result, it has been suggested that general environmental factors (i.e., lifestyle, alimentation [diet]) were likely critical for enhanced carcinogenesis in the gut and colorectal carcinoma development, and these outcomes were being influenced through possible changes in the local intestinal environment (e.g., commensal microflora) that variously impacted upon the mucosal components, including immune system cells (Tlaskalova-Hogenova et al, 2004;McGarr et al, 2005).…”
Section: Introductionmentioning
confidence: 99%